2016
DOI: 10.1186/s12889-016-3090-1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality in diabetes in Yaounde, Cameroon: a relation with precipitation and temperature

Abstract: BackgroundDiabetes is a growing health concern in developing countries, with Cameroon population having an estimated 6% affected. Of note, hospital attendees appear to be increasing all over the country, with fluctuating numbers throughout the annual calendar. The aim of the study was to investigate the relationship between diabete hospitalization admission rates and climate variations in Yaounde.MethodsA retrospectively designed study was conducted in four health facilities of Yaounde (Central Hospital, Unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 34 publications
3
17
0
Order By: Relevance
“…However, many studies have shown that nonadherence on insulin therapy has been considered the main cause of DKA particularly in low-income countries 11,[13][14][15] . Based on the literature, the precipitating factors of DKA are different between countries and depend on number of variables such as age, climate, education level and economic level 6,13,16 .…”
Section: Introductionmentioning
confidence: 99%
“…However, many studies have shown that nonadherence on insulin therapy has been considered the main cause of DKA particularly in low-income countries 11,[13][14][15] . Based on the literature, the precipitating factors of DKA are different between countries and depend on number of variables such as age, climate, education level and economic level 6,13,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Neem oil is equally applied as a pomade to treat "getti getti" (nappy rash) [2][3][4][5]. In the South West region of Cameroon, Azadirachta indica A. Juss seeds, leaves and bark are used to treat malaria, typhoid, intestinal worms and diabetes, and used as mosquito repellent [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus is a group of metabolic diseases characterized by elevated blood glucose levels resulting from defects in insulin secretion, insulin action, or both. The chronic hyperglycemia of diabetes is associated with long term damage, dysfunction, and failure of various organs, especially the eyes, kidneys, nerves, heart, and blood vessels [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations